Tapped In - Jian Jones; Hakeem Leonard; Khalilah Johnson (Voices, 2025)
“Tapped In: A Collaborative Thought Approach on Reimagining Positionality, Hip Hop, and Therapy Education” explored the processes of three Black therapy educators in predominantly white higher education programs and professions. Two occupational therapistsand one music therapist posed the research question: How does Hip Hop identity influence educational practice and praxis for Black therapy educators? The authors collaborated in acquiring autoethnographic data revealing their stance as tapped-in, tapped-out, and untapped educators. Tap-in, a Hip Hop colloquialism, signifies connection. As tapped-in educators, the authors described their experiences in connectedness with Hip Hop culture while doing, being, and becoming within academia; the progression of life as occupational beings in the role of educators. Findings from thematic analysis exposed collaborative Hip Hop associated themes of Black identity, Black intellectualism, theory, and pedagogy. This article provides considerations for Black academics; toreimagine Hip Hop Futurism as Hip Hop Futurism for Therapy Education. With Hip Hop Futurism for Therapy Education, educators seek to create a more inclusive, diverse, and just future that will empower therapy students, educators, and stakeholders to shapetheir destinies in the face of rapid social change.